Performance Analysis of KNN and BERT Algorithms for Classifying Student Sentiments Towards Campus Services - Mutmainna, Mutmainna; Hamrul, Heliawati; Firgiawan, Wawan (Journal of Applied Informatics and Computing, 2026)
This study addresses the limitations of campus service evaluation processes that are still conducted manually and are unable to optimally process students’ textual opinions. The objective of this research is to analyze and compare the performance of the K-Nearest Neighbor (KNN) and BERT algorithms in classifying student sentiments toward campus services. The research stages include text preprocessing, the generation of IndoBERT embeddings for the KNN model, and fine-tuning IndoBERT for direct sentiment classification. The dataset consists of student evaluation texts from the Faculty of Engineering at UNSULBAR, labeled as negative, neutral, and positive sentiments. Model evaluation is performed using accuracy, precision, recall, and F1-score metrics. The results show that the basic KNN model achieves an accuracy of 79%, while KNN with hyperparameter tuning improves performance to 86%. The BERT model delivers the best performance, achieving an accuracy of 88.68%, precision of 87.87%, recall of 90.19%, and an F1-score of 88.79%. These findings indicate that transformer-based approaches, particularly IndoBERT, are more effective in understanding the contextual nuances of student language than traditional methods, and are therefore more recommended for sentiment analysis implementation in campus service evaluation.